2018
DOI: 10.1038/s41401-018-0157-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-11-keto-β-boswellic acid suppresses docetaxel-resistant prostate cancer cells in vitro and in vivo by blocking Akt and Stat3 signaling, thus suppressing chemoresistant stem cell-like properties

Abstract: Acquired docetaxel-resistance of prostate cancer (PCa) remains a clinical obstacle due to the lack of effective therapies. Acetyl-11-keto-β-boswellic acid (AKBA) is a pentacyclic triterpenic acid isolated from the fragrant gum resin of the Boswellia serrata tree, which has shown intriguing antitumor activity against human cell lines established from PCa, colon cancer, malignant glioma, and leukemia. In this study, we examined the effects of AKBA against docetaxel-resistant PCa in vitro and in vivo as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 42 publications
0
18
0
1
Order By: Relevance
“…15 Liu indicated that AKBA inhibits the proliferation and cancer stem cell-like properties of docetaxel resistant prostate cancer cells in vitro and in vivo via blocking Akt and Stat3 signaling. 16 However, the potential therapeutic effect and the underlying molecular mechanism of AKBA on breast tumor have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…15 Liu indicated that AKBA inhibits the proliferation and cancer stem cell-like properties of docetaxel resistant prostate cancer cells in vitro and in vivo via blocking Akt and Stat3 signaling. 16 However, the potential therapeutic effect and the underlying molecular mechanism of AKBA on breast tumor have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Our animal experiments verified the findings of in vitro experiments. Previous research confirmed that AKBA has an anti-tumor effect in nude mice[ 2 - 4 , 33 , 42 , 43 ]. Our results indicate that the tumor size of AKBA-treated nude mice is significantly smaller compared to the control group.…”
Section: Discussionmentioning
confidence: 81%
“…The molecular structure of AKBA is shown in Figure 1 . AKBA is anti-inflammatory agent that exhibits potent cytotoxic activities against various types of tumors, such as hepatocellular carcinoma[ 2 ], glioblastoma[ 3 ], prostate cancer[ 4 ], lung carcinogenesis[ 5 ], colon cancer[ 6 , 7 ], and leukemia[ 8 , 9 ]. However, the efficacy and mechanism of action of AKBA in treating gastric cancer have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, AKBA was found responsible for the suppression of VEGFR2-mediated angiogenesis in prostate cancer [101]. Studies by Liu et al, showed that AKBA suppressed docetaxel-resistant prostate cancer cells via blockage of STAT3 and Akt signaling pathways [138]. A semi-synthetic triterpenoid derivative, 3-cinnamoyl-11-keto-beta-BA (C-KβBA), demonstrated specific antiproliferative and proapoptotic effects in cancer cell lines such as PC-3, LnCaP, and DU-145, as well as in PC-3 prostate cancer xenografts, by downregulating the activation of p70 ribosomal S6 kinase [122].…”
Section: Potential Role Of Bas In the Treatment Of Chronic Diseasesmentioning
confidence: 99%